How to identify epistemic injustice in global health research funding practices: a decolonial guide. Issue 4 (25th April 2022) - Koum Besson, Emilie S
Abstract : Epistemic injustice is a growing area of study for researchers and practitioners working in the field of global health. Theoretical development and empirical research on epistemic injustice are crucial for providing more nuanced understandings of the mechanisms and structures leading to the exclusion of local and marginalised groups in research and other knowledge practices. Explicit analysis of the potential role of epistemic injustice in policies and practices is currently limited with the absence of methodological starting points. This paper aims to fill this gap in the literature by providing a guide for individuals involved in the design and review of funding schemes wishing to conduct epistemic injustice analysis of their processes using a decolonial lens. Placing contemporary concerns in a wider historical, political and social context and building from the intertwined issues of coloniality of power, coloniality of knowledge and coloniality of being that systematically exclude non-Western epistemic groups, this practice paper presents a three-step decolonial approach for understanding the role and impact of epistemic injustices in global health research funding. It starts with an understanding of how power operates in setting the aim of a call for research proposals. Then, the influence of pose and gaze in the review process is analysed to highlight the presence of epistemological colonisation before discussing methods to address the current funding asymmetries by supporting new ways of being and doing focused on knowledge plurality. Expanding research on how epistemic wrongs manifest in global health funding practices will generate key insights needed to address underlying drivers of inequities within global health project conception and delivery.